Osteoarthrosis in a rural South African Negro population. Issue 3 (June 1976) - Solomon, L; Beighton, P; Lawrence, J S
Abstract : The prevalence and distribution of osteoarthrosis has been studied in a South African Negro population. One or more joints were affected in 60% of the males and 48% of the females, compared with a prevalence of 55% in males and 63% in females in a comparable English population. Multiple osteoarthrosis was significantly less common in the African than in the English population, the difference here being greatest in females. Clinical Heberden's nodes were also very infrequent in the African population. However, the Tswana males had significantly more osteoarthrosis of the metacarpophalangeal and proximal interphalangeal joints than was encountered in English males. This is attributed to the traumatic effect of hard manual work which is carried on into old age among most African populations.